Smart Home and Thermal Imaging Technology for COVID 19 Detection Using the Internet of Things (IoT) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
The Internet of Things (IoT) is a technological advancement that is rendering the world progressively intelligent. Without IoT technology, the concept of a connected world would be inconceivable. The number of people infected with the coronavirus is on the rise. Most of them are ignorant about the virus's most common symptoms: fever or high body temperature. Owing to the rapid spread of the disease, infrared thermometers are being used everywhere to measure body temperature in places with a large population. This action is extremely effective in stopping the disease from spreading. This study identifies and outlines the features of current infrared imaging technology for thermal imaging in smart home doorbell technologies, as well as their benefit in detecting the covid-19. This technology makes use of infrared rays that are naturally emitted from the skin's surface. When a high-temperature body is detected, the thermal camera generates infrared spectra with high-intensity levels. Virtual Reality (VR) was also used to monitor and manipulate the cameras, and it was connected to the IoT. This smart doorbell system uses an infrared temperature sensor to detect visitors' body temperatures as they approach. If the doorbell detects a temperature, it will trigger a sound and illuminate corresponding LED lights to warn the visitor. The screening procedure, which involves the detected face and the detected body temperature, will be shown on the monitor. A visitor will be given an alert if their body temperature is too high.